Efficient Organic Solar Cell with 16.88% Efficiency Enabled by Refined Acceptor Crystallization and Morphology with Improved Charge Transfer and Transport Properties. Issue 18 (20th March 2020) - Zhu, Lei; Zhang, Ming; Zhou, Guanqing; Hao, Tianyu; Xu, Jinqiu; Wang, Jing; Qiu, Chaoqun; Prine, Nathaniel; Ali, Jazib; Feng, Wei; Gu, Xiaodan; Ma, Zaifei; et al.
Abstract: Single‐layered organic solar cells (OSCs) using nonfullerene acceptors have reached 16% efficiency. Such a breakthrough has inspired new sparks for the development of the next generation of OSC materials. In addition to the optimization of electronic structure, it is important to investigate the essential solid‐state structure that guides the high efficiency of bulk heterojunction blends, which provides insight in understanding how to pair an efficient donor–acceptor mixture and refine film morphology. In this study, a thorough analysis is executed to reveal morphology details, and the results demonstrate that Y6 can form a unique 2D packing with a polymer‐like conjugated backbone oriented normal to the substrate, controlled by the processing solvent and thermal annealing conditions. Such morphology provides improved carrier transport and ultrafast hole and electron transfer, leading to improved device performance, and the best optimized device shows a power conversion efficiency of 16.88% (16.4% certified). This work reveals the importance of film morphology and the mechanism by which it affects device performance. A full set of analytical methods and processing conditions are executed to achieve high efficiency solar cells from materials design to device optimization, which will be useful in future OSC technology development. Abstract : A power conversion efficiency of 16.88% (certified as 16.4%) is achieved based on PM6:Y6 by morphology optimization, which is the most efficient for organic solar cells. Through the study of single structure and film morphology, a well‐ordered 2D crystal is found, which helps to enhance ultrafast hole and electron transfer, thus improving performance.